Potencial biotecnológico e tolerância à restrição hídrica de sementes de Erythrina velutina Willd - Souza, Juliana Lopes (2020)
Erythrina velutina is a native Brazilian tree species with wide occurrence in arid and humid regions, observed in Caatinga, Atlantic Forest and Cerrado. As pioneer species, it is highly recommended for the reforestation of degraded areas and its orthodox seeds have tolerance to desiccation and water deficit. E. velutina’s seeds are stored as the main ex situ conservation resource and are widely used by traditional medicine. These aspects emphasize the high relevance of conservation and study of this natural resource, especially in face of the impacts caused to the environment by climate change. Therefore, the objective of this study was to evaluate the physiological characteristics of E. velutina’s seeds under water stress, identifying deterioration levels, tolerance mechanisms and biotechnological potential. To evaluate the biotechnological potential of this species, scientific data were prospected from articles, patents and nucleotide sequences related to E. velutina. Despite the low number of patents and nucleotides sequenced for the species, scientific data establishes it as prominent and with high biotechnological potential in the fields of pharmacy, bioactive compounds and source of polynucleotides and polypeptides for the insertion of abiotic stress tolerance. Although orthodox and longevous, E. velutina’s seeds are susceptible to deterioration during storage. When evaluating the viability and vigor of lots from this species, it was identified that x-ray images analysis, associated to the evaluation of the internal density of seeds, differentiates seeds with higher germination capacity in lots of moderate deterioration. Consequently, it is possible to select and optimize the propagation of the species using a non-destructive method of analysis. In addition to storage deterioration, E. velutina’s seeds can be affected by environmental stresses. Analyzing the viability and vigor of the seeds, this time under water deficit, it was observed the ability to tolerate water stress, demonstrated by germination under osmotic potentials. To recover from seed damage and create a cross-tolerant condition, the synthesis of protective proteins such as LEA and sHSP is stimulated through osmotic conditioning. In osmoconditioned E. velutina’s seeds, though RT-qPCR it was identified the increase in expression of Em6 (LEA group 1) and sHSP genes, characterizing a condition of resistance to drought stress. Erythrina velutina is a species with several biotechnological properties, germinative recovery capacity deterioration and water stress tolerance, being an important plant genetic resource with potential adaptability to climate change.